TEKNIS OPERASIONAL PENGELOLAAN SAMPAH DI DESA NAGRAK DAN DESA CIANGSANA MENUJU TPST 3R - Muharam, Gusni; Ruhiyat, Ratnaningsih; Minarti, Astari (Jurnal Lingkungan dan Kota, 2023)
Nagrak and Ciangsana Village located in Gunung Putri Sub-district, Bogor Regency, West Java. The area of Nagrak Village is 5.84 km2 and the area of Ciangsana Village is 8.62 km2. The level of waste service in both villages is 12%, the planned service level target at the end of the planning year 2032 is 100%. This planning data collection uses the SNI 19-3964-1994 method regarding data collection methods in operational technical planning for waste management. Sampling using the stratified random sampling method, the waste generation rate in Nagrak Village and Ciangsana Village is 2 liters/person/day with a total population of 51488 people from the two villages, the waste generation from domestic areas has 54% organic waste and anorganic waste has 46%. The waste generation from Non-domestic areas has 60% organic waste and anorganic waste has 40%. Organic waste is processed with Black Soldier Fly (BSF), anorganic waste is processed with the Refused Derived Fuel (RDF) method at TPST 3R Trisakti. The planning stage consists of short term (2022-2024) medium term (2025-2028) and long term (2029-2032). The cost budget plan includes investment, operational and maintenance costs with a total cost of Rp.59,424,025,515. The selected alternative is alternative I, which has a more economical and affordable cost budget for Nagrak Village and Ciangsana Village.